Tumor Contrast-Enhancement for Monitoring of PRRT 177Lu-DOTATATE in Pancreatic Neuroendocrine Tumor Patients - Pettersson, Olof; Fröss-Baron, Katarzyna; Crona, Joakim; Sundin, Anders (Frontiers in Oncology, 2020)
Background: Therapy monitoring of cancer treatment by contrast-enhanced CT (CECT), applying response evaluation criteria in solid tumors criteria version 1.1 (RECIST 1.1) is less suitable for neuroendocrine tumors (NETs) which, when responding, tend to show stabilization rather than shrinkage. New methods are needed to further classify patients in order to identify non-responders at an early stage and avoid unnecessary adverse effects and costs. Changes in arterial tumor attenuation and contrast-enhancement could be used to identify the effect of therapy, perhaps even in early stages of treatment. Methods: Patients with metastatic pancreatic NETs (PNETs) receiving peptide receptor radionuclide therapy (PRRT) with 177Lu-DOTATATE underwent CECT at baseline, mid-treatment (PRRT cycles 3-5) and at follow-up, three months after the last PRRT cycle. At baseline CECT, the liver metastasis with the highest arterial attenuation was identified in each patient. The fold changes in arterial tumor attenuation (Hounsfield Units, HU), contrast-enhancement (HU) and transversal tumor area (cm2) between CECT at baseline, mid-treatment and follow-up were calculated. Correlation of the tumor metrics to outcome parameters such as progression-free survival (PFS) and time to best response was performed. Results: Fifty-two patients were included (27 men, 25 women), median age 60 years (range 29-80), median Ki-67 8% (range 1-30). Six patients had grade 1 PNETs, forty had grade 2 and four had grade 3 tumors. As an internal control, it was first tested and established that the tumor contrast-enhancement was not merely related to that of the abdominal aorta. The mean±SD arterial attenuation of the liver metastases was similar at baseline, 217±62 HU and at mid-treatment, 238±80 HU and then decreased to 198±62 HU at follow-up, compared to baseline (p=0.024, n=52) and mid-treatment (p=0.0004, n=43). The transversal tumor area decreased 25% between baseline and follow-up (p=0.013, n=52). Tumor contrast-enhancement increased slightly from baseline to mid-treatment and these fold changes correlated with PFS (R2=0.33, p=0.0002, n=37) and with time to best response (R2=0.34, p<0.0001, n=37). Conclusions: Early changes in contrast-enhancement and arterial attenuation in PNET liver metastases may for CECT monitoring of PRRT yield complementary information to evaluation by RECIST 1.1.